Beyond business: Exploring the social engagement of entrepreneurs in Phnom Penh, Cambodia - Ban, Bunheng; You, Vithyea; Sario T., Pio (MASI Mandiri Edukasi, 2024)
The current article aims to shed light on the social engagement practices of businesses in Phnom Penh, Cambodia, and to inform readers about those practices. In particular, the article examines how entrepreneurs engage in social activities, establish communication with their contemporaries, and advocate for entrepreneurship. The data was collected from a representative sample of business owners while employing a quantitative research design to determine how much business owners participate in social activities. The ongoing research has yielded preliminary findings and conclusions. The findings reveal that entrepreneurs have high social engagement through active participation in mentoring programs, knowledge-sharing activities, and networking events. They demonstrated their participation in these activities. The findings shed light on the significance of social capital and the growth of communities within the framework of Phnom Penh's environment for entrepreneurial endeavours. The implications of this study for policy, practice, theory, and future research, emphasizing the need to foster a culture that encourages social activity among entrepreneurs and fosters a supportive environment, were discussed. The study adds to the expanding body of literature on entrepreneurship by highlighting the diverse features of entrepreneurial pursuits and the importance of social engagement that extends beyond corporate objectives. Future studies should be conducted with a bigger sample size and scope.